EFEKTIFITAS PELVIC ROCKING EXERCISES DENGAN BIRTHING BALL TERHADAP LAMA WAKTU PERSALINAN PADA IBU PRIMIPARA - Surtiningsih Surtiningsih; Linda Yanti; Arlyana Hikmanti; Fauziah Hanum Nur Adriani; Feti Kumala Dewi (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
Prolonged labor causes complications for both mother and baby. Pelvic Rocking Exercised (PRE) helps shorten the length of the first and second stages and minimizes prolonged labor. The purpose of this study was to determine the effectiveness of PRE with or without Birthing Ball (BB) on the duration of the first and second stage of labor. The research method used is quasi-experimental, on 57 respondents, posttest only control design and One way Anova statistical test. The results showed that the characteristics of the respondents obtained an average age of 23-24 years, gestational age 39 weeks, uterine fundal height 29-30 cm, and baby birth weight 2992-3037 grams. The average length of the first stage of labor with PRE was 163.75 minutes, PRE with BB 180.59 minutes, and the control group was 380 minutes, while the length of the second stage was PRE 40.10 minutes, PRE With BB 47 minutes, and the control group was 57 minutes. There was a difference in the length of the first stage of labor with PRE with data without BB, with the control group p = 0.000 0.05, and there was a difference in the average length of the second stage of labor in the second stage of labor in women with PRE, PRE with or without BB with control group p=0,0000,05. Conclusion PRE with and without Birthing Ball is effective in shortening the length of labor in the first stage and the second stage.